Structured lipids: methods of production, commercial products and nutraceutical characteristics - Zam, Wissam (Progress in Nutrition, 2015)
Structured lipids (SLs) are generally defined as triacylglycerols (TAGs) that have been modified to change the fatty acid composition and/or their positional distribution in glycerol molecules by chemical and/or enzymatic reactions and/or by genetic engineering processes. They are designed for obtaining TAGs with improved functional properties (i.e. fats with specific physical properties for food applications) and/or for medical and nutritional applications, especially to meet for the growing need for healthier foods and to prevent obesity, cancer and cardiovascular disease cardiovascular disease. Production methods of SLs and commercial products examples are discussed in this review. Moreover, nutritional and medical uses of SLs and their effect on human health are also reviewed in this paper.